Klebsiella pneumoniae yggG gene product: a zinc-dependent metalloprotease - Kuan, Chee Sian; Wong, Mun Teng; Choi, Sy Bing; Chang, Ching Ching; Yoke, Hiang Yee; Abdul Wahab, Habibah; Mohd Yahaya, Normi; Wei, Cun See Too; Few, Ling Ling (Multidisciplinary Digital Publishing Institute, 2011)
Klebsiella pneumoniae causes neonatal sepsis and nosocomial infections. One of the strains, K. pneumoniae MGH 78578, shows high level of resistance to multiple microbial agents. In this study, domain family, amino acid sequence and topology analyses were performed on one of its hypothetical protein, YggG (KPN_03358). Structural bioinformatics approaches were used to predict the structure and functionality of YggG protein. The open reading frame (ORF) of yggG, which was a putative metalloprotease gene, was also cloned, expressed and characterized. The ORF was PCR amplified from K. pneumoniae MGH 78578 genomic DNA and cloned into a pET14-b vector for heterologous expression in Escherichia coli. The purified YggG protein was subsequently assayed for casein hydrolysis under different conditions. This protein was classified as peptidase M48 family and subclan gluzincin. It was predicted to contain one transmembrane domain by TMpred. Optimal protein expression was achieved by induction with 0.6 mM isopropyl thiogalactoside (IPTG) at 25 °C for six hours. YggG was purified as soluble protein and confirmed to be proteolytically active under the presence of 1.25 mM zinc acetate and showed optimum activity at 37 °C and pH 7.4. We confirmed for the first time that the yggG gene product is a zinc-dependent metalloprotease.